Signifikansi Diklat, Remunerasi dan Organizational Citizenship Behavior Atas Performansi Kerja: (Studi PT. Bank Rakyat Indonesia Kudus) - Aditya Angger Wibowo (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the influence of training, remuneration, and Organizational Citizenship Behavior (OCB) on the work performance of employees of PT. Bank Rakyat Indonesia Kudus Branch. Using an explanatory research design, this study examines the causality relationship between variables within the framework of human resource management. The study population included 155 employees, with a final sample of 112 respondents determined through purposive sampling. Primary data was collected through a validated and reliable questionnaire, then analyzed using multiple linear regression, t-test, F-test, and determination coefficient. The results of the study show that training, remuneration, and OCB have a positive and significant effect on work performance, both partially and simultaneously. In particular, OCB has been proven to strengthen social cohesion and operational efficiency in work teams. These findings confirm that competency development through adaptive training, a transparent compensation system, and the internalization of voluntary behavior outside of formal duties are fundamental factors in increasing organizational productivity. The practical implications of this study encourage banking management to invest strategically in human resource development and employee welfare restructuring, in order to strengthen emotional attachment, professionalism, and sustainability in achieving organizational targets.